Dinamika Check & Balance Antar Lembaga Negara di Indonesia Pada Masa Periode Kedua Presiden Jokowi - Siregar, Muhammad Akbar; Lubis, Joice Natalia; Siregar, Patrecia Gabriella; Sitompul, Novita Sari (Indonesian Journal Publisher, 2025)
This study examines the dynamics of inter-institutional relations among the executive, legislative, and judicial branches in Indonesia during the second term of President Joko Widodo, focusing on the implementation of the check and balanceprinciple. Employing a library research method, the study analyzes secondary sources such as academic journals, news reports, official documents, and public statements to assess the effectiveness of institutional oversight mechanisms. The findings indicate a growing imbalance of power, with executive dominance, weakened legislative oversight, and reduced judicial independence. Political consolidation and the revision of key laws have further reinforced this trend. Overall, the check and balancemechanism has not functioned effectively during this period, raising concerns about the state of democracy and the rule of law in Indonesia.